Capital Controls and International Portfolio Theory : A Microeconomic Approach - Rose, Marjorie (IMF Working Papers; Working Paper ;, 1990)
This paper examines the effects of capital controls on asset prices. A closed-form valuation model by Eun and Janakirimanan (1986) is extended to analyze the impact of three restrictions on international portfolio investment: a percentage quantity constraint on the amount of foreign securities a domestic resident may hold in her portfolio; a constraint on the absolute amount of foreign securities a domestic resident may hold; and a percentage tax on the domestic purchase price of a foreign security. Comparative statics and numerical analysis are used to reveal the effects of these distortions on domestic and world equilibrium prices.